2022
DOI: 10.1371/journal.pone.0265933
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with acute respiratory infection among under-five children in selected tertiary hospitals of Kathmandu Valley

Abstract: Background Acute respiratory infection (ARI) is responsible for about 30–50 percent of visits to health facilities and for about 20–30 percent of admissions to hospitals in Nepal for children under 5 years old. Incidence of ARI in children among under-five years of age is 344 per 1000 in Nepal. Hence, the study aims to find out the prevalence and factors associated with acute respiratory infection among under-five children. Methods A cross-sectional study was conducted at Nepal Medical College and Teaching H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
5
11
3
1
Order By: Relevance
“…The overall prevalence recorded in this study is lower than the reports from some other parts of the globe, 7,22 but a confirmation of the observation by UNICEF that the majority of ARI instances or conditions and mortalities as documented from some of the infected children, are in from the sub-Saharan countries. 23,24 Aside Cameroon which has 1% prevalence of ARI among the under-5 children, other studied countries had higher prevalence of the ARI but not as high as have been reported by studies in Nigeria, 25 Ethiopia 18 and another that comprised some African countries 7 as well as from a Nepalese 26 and an Indian studies. 27 The discoveries could be explained by inadequate wealth-related and education status of mothers, insufficient supply of water, the prevalence of communicable diseases, and poor nutrition knowledge, that are more predominant in many Sub-Saharan countries when compared to their developed counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence recorded in this study is lower than the reports from some other parts of the globe, 7,22 but a confirmation of the observation by UNICEF that the majority of ARI instances or conditions and mortalities as documented from some of the infected children, are in from the sub-Saharan countries. 23,24 Aside Cameroon which has 1% prevalence of ARI among the under-5 children, other studied countries had higher prevalence of the ARI but not as high as have been reported by studies in Nigeria, 25 Ethiopia 18 and another that comprised some African countries 7 as well as from a Nepalese 26 and an Indian studies. 27 The discoveries could be explained by inadequate wealth-related and education status of mothers, insufficient supply of water, the prevalence of communicable diseases, and poor nutrition knowledge, that are more predominant in many Sub-Saharan countries when compared to their developed counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies, many families lived in substandard housing or remained exposed to toxins, pollutants, and infections due to low incomes and occupational constraints [ 23 - 25 ]. Previous research found that children who were in the kitchen while food was being cooked were twice as likely to develop symptoms of ARIs as those who were not in the kitchen [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed no significant association between ARI symptoms in children and age, sex, type of toilet used, drinking water sources, exclusive breastfeeding, number of siblings, or marital status as reported by the households. However, several studies have revealed strong correlations between socio-demographic characteristics and symptoms [ 19 , 26 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian sebanyak 286 anak dalam penelitian ini, lebih dari separuh anak (64%) berusia 24 bulan ke atas dan relatif sama persentase anak (62,2%) berjenis kelamin laki-laki, sedangkan 11,5% anak lahir premature 7,3% diantaranya adalah anak dengan berat badan lahir rendah, status gizi, sebagian besar anak-anak (97,9%) berstatus gizi normal dan 60,5% anak mendapat ASI eksklusif, sementara sebagian besar mereka (96,2%) telah menyelesaikan imunisasi sesuai usia., 24,1% tinggal di rumah yang terlalu padat rumah dan 23,1% memiliki ventilasi yang buruk (11) Penelitian yang dilakukan oleh Agusriyani dan Aliah (12) , hasil penelitian diperoleh adanya hubungan antara ventilasi, pencahayaan, pengetahuan dan kepadatan hunian dengan kejadian Infeksi saluran pernapasan akut. Penelitian oleh Fathmawati, Rauf, Indraswari (4) hasilnya menunjukkan bahwa ibu yang bekerja lebih berisiko terkena ISPA dan air tanah sebagai sumber air merupakan faktor protektif terhadap terjadinya ISPA pada balita.…”
Section: Pendahuluanunclassified